Development of Sustainable and Functional Fabrics from Recycled and Nanocomposite Polyester Fibers - Solomon Addis; Hermela Ejegu; Messay Dubale; Wondwossen Mamuye (Advances in Materials Science and Engineering)
Antimicrobial knitted and woven fabrics were developed from recycled polyester (PET) and silver nanocomposite (SNC) fibers. Two different fabrics were produced from two different blend proportions of the fibers. The antimicrobial properties of fabrics were tested against those of the S. aureus (Gram-positive) and E. coli (Gram-negative) bacterial natures, and their yarn properties and hand-related characteristics were investigated. The results show uneven fabrics properties such as irregularity in thickness and SNC-recycled PET fiber ratio increase, and the tensile strength decreases while the NEP number increases. This implies that fabrics made from a blend with higher SNC-recycled PET fiber ratios have higher surface roughness levels, higher bending rigidity, and harder texture. As a consequence, the antimicrobial efficiency of the fabrics was improved as the percentage of SNC increased. The recycled PET fiber within the blended yarn shows a good antimicrobial property (above 90%) observed in all fabrics. The reduction of bacterial colonies was constantly exceeding 90% for both E. coli and S. aureus in all fabric samples.